Facts and States of Affairs: from ontological logic to language use - Polakof, Ana Clara (Virtualia Journal, 2020)
We argue that it is possible to differentiate facts from states of affairs ontologically and that it those differences are reflected in language use. We propose a platonist ontology, based on Chateaubriand (2001 and 2005), hierarchized in levels and types. It contains (starting from level 0) concrete objects as the most basic entities, logical and non logical properties, facts, states of affairs, among others. While some current philosophers (as Chateaubriand, 2001 and Armstrong, 1997) treat facts and states of affairs as synonyms, we argue that it is possible to defend that they are different and that this differentiation is advantageous. We try to show that –once we have differentiated through an ontological logic (cf. Chateaubriand, 2001) facts from states of affairs– it is possible to relate those arguments to language use and we try to show that the ontological differences are reflected on the structures used to identify those entities.